Identifying Key Drivers of Efficient B Cell Responses: On the Role of T Help, Antigen-Organization, and Toll-like Receptor Stimulation for Generating a Neutralizing Anti-Dengue Virus Response - Sobczak, Jan M.; Barkovska, Irena; Balke, Ina; Rothen, Dominik A.; Mohsen, Mona O.; Skrastina, Dace; Ogrina, Anete; Martina, Byron; Jansons, Juris; Bogans, Janis; Vogel, Monique; Bachmann, Martin F.; et al. (Vaccines (Basel), 2024)
T help (Th), stimulation of toll-like receptors (pathogen-associated molecular patterns, PAMPs), and antigen organization and repetitiveness (pathogen-associated structural patterns, PASPs) were shown numerous times to be important in driving B-cell and antibody responses. In this study, we dissected the individual contributions of these parameters using newly developed “Immune-tag” technology. As model antigens, we used eGFP and the third domain of the dengue virus 1 envelope protein (DV1 EDIII), the major target of virus-neutralizing antibodies. The respective proteins were expressed alone or genetically fused to the N-terminal fragment of the cucumber mosaic virus (CMV) capsid protein—nCMV, rendering the antigens oligomeric. In a step-by-step manner, RNA was attached as a PAMP, and/or a universal Th-cell epitope was genetically added for additional Th. Finally, a PASP was added to the constructs by displaying the antigens highly organized and repetitively on the surface of CMV-derived virus-like particles (CuMV VLPs). Sera from immunized mice demonstrated that each component contributed stepwise to the immunogenicity of both proteins. All components combined in the CuMV VLP platform induced by far the highest antibody responses. In addition, the DV1 EDIII induced high levels of DENV-1-neutralizing antibodies only if displayed on VLPs. Thus, combining multiple cues typically associated with viruses results in optimal antibody responses.